Complications Of Secondary Immunodeficiency, Diagnosis and Treatment of Leukopenia in Patients with Acute Leukemia - Shakhobidinov Nohidbek Vohidjon ugli; Yuldasheva Nodira Ergashevna (Genius Journals, 2023)
The characteristic manifestations of NL are intracranial hypertension, meningeal syndrome, and cytosis in the cerebrospinal fluid. However, on the one hand, there has not yet been an idea of the course of NL with modern tactics for the treatment of acute hemoblastoses, on the other hand, the appearance of even reduced neurological symptoms significantly worsens the clinical course of the disease, aggravates the prognosis and requires an immediate change in the tactics of therapy
Keywords: intracranial hypertension; meningeal syndrome; cytosis